Well- or Ill-Posed Problem of Parameter Identification –The Method of Analysis Applied in a Cassette Recorder Drive Modeling - Kowalska, Z. (Engineering Transactions, 2015)
In the paper, the method of error analysis of physical parameter estimates identified by the least-squares fitting of the dynamical model characteristics to the corresponding experimental data points, measured (observed) with systematic errors, is discussed. The quantity measures of global sensitivity of parameter estimate to the observation errors are introduced. The formulas for computing the derivatives of parameter estimates with respect to the observation errors are derived. The advantages of the method are illustrated by the example of application of the method in the modeling process of a tape recorder drive at the stage of experiment design.